Neuromyelitis optica in a 9 year old girl: A case report - Seth, Soutrik; Biswas, Tanmoy; Das, Rajib; Roy, Atanu (Asian Journal of Medical Sciences, 2016)
Neuromyelitis optica (NMO) is an acquired demyelinating disorder affecting the optic nerves and spinal cord either simultaneously or sequentially. Prognosis is guarded particularly for the optic neuritis.We report here a case of first attack of NMO occurring in a 9 year old girl child coming from a rural area of Burdwan. Asian Journal of Medical Sciences Vol.7(5) 2016 132-134